(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
Public transportation is carried out through its various means by securing the daily movement of people, and it aims to transport them from the starting point to the arrival point in the fastest time and at the lowest possible cost, and this paper: Sheds Light on the concept of multi-model transport network, and it shows the importance of studying public transportation as integrated system By connecting all means of transport to connecting points of spatial and temporal dimension in the city of Lattakia, and the most important results research findings: The Network Analyst- ArcGIS 10.5. It enabled us to convey a true picture of the reality of bus transportation in Lattakia city centers by giving accurate information about the journey in all its stages, which takes less than half an hour within the city center. It turns out that the lost time during the trip is due to the slow transportation, But also about the time violated outside the mode of transportation, including the waiting time on the stops.